Prevalence, correlates and trends of intimate partner violence among Indigenous and northern youths in the Northwest Territories, Canada - Malama, Kalonde; Admassu, Zerihun; Logie, Carmen H.; Lys, Candice L.; Kanbari, Amanda; Taylor, Shira B.; Mackay, Kayley Inuksuk; McNamee, Clara; Gittings, Lesley (Journal of global health reports, 2024)
# Background Intimate partner violence (IPV) is rising in Canada and disproportionately affects Indigenous communities in the Northwest Territories largely due to the harmful, ongoing effects of settler colonialisation. Youth are known to be at high risk for IPV, but scant evidence exists about the scale of IPV and strategies for its prevention among youth in the Northwest Territories of Canada. # Methods We conducted a serial cross-sectional study that measured the prevalence, correlates and four-year violence trends among youths participating in a land- and arts-based programme in the Northwest Territories. Researchers recruited 240 youths aged 12 to 19 to participate in an Indigenous-led land- and arts-based retreat designed to promote resilience, empowerment, and relational well-being among youth. The study period was from 2018 to 2021, and each annual retreat contained a mix of new and returning participants. At each retreat, participants were asked to report, in a self-administered survey, if they had experienced or perpetrated IPV in the past 12 months. # Results Youths reported a high prevalence of experiencing (62%) and perpetrating (55%) IPV. For every one-unit increase in depression severity score, participants were 30% more likely to experience IPV) and 24% more likely to perpetrate IPV. Although the prevalence of experiencing and perpetrating IPV decreased by 6% and 14%, between 2018 and 2021, this trend was not statistically significant. # Conclusions The high prevalence of IPV, linked to depression among youths in our study, calls for integrated mental health and violence prevention programming with youth in the Northwest Territories. Future programmes should use a strengths-based and decolonised approach to address the underlying effects of settler colonialism on the social dynamics that sustain IPV in Northern and Indigenous communities.